Decarbonisation and wholesale electricity market design1. (31st July 2018) - Nelson, Tim; Orton, Fiona; Chappel, Tony
Abstract : In recent decades, many power systems have introduced electricity generator competition. Market designs have varied with some countries adopting 'energy‐only' markets and others utilising capacity remuneration mechanisms. With increasing deployment of cost competitive renewable energy and the introduction of policy measures to reduce greenhouse gas emissions, concerns are emerging about the sustainability of these market designs. In Australia, wholesale electricity prices have increased markedly – the result of a 'disorderly' transition away from coal to new renewable energy. This paper critically examines the 'energy‐only' market in a high‐penetration renewables system, with a particular focus on the vertically and horizontally restructured National Electricity Market (NEM). We propose that the 'energy‐only' market can indeed work within a decarbonised energy system. But as renewables increasingly replace coal‐fired power stations, 'unintended consequences' will need to be addressed to facilitate an 'orderly' transition. It will be important that policy ensures appropriate new investment in firm capacity is forthcoming; and pricing outcomes are acceptable given political economy constraints.